Issues of contemporary wind engineering and aerodynamics of building structures - Tomasz Lipecki; Paulina Jamińska (Budownictwo i Architektura, 2016)
The paper reviews nowadays problems and issues of wind engineering and aerodynamics of building structures. The article mainly focuses on aerodynamics of building structures, shortly characterizing theoretical bases, which one must take into account when assuming wind loads. The three different approaches of collecting information in the field of wind loads are described: in-situ measurements, wind tunnel tests and numerical simulations. Also, a review of the most important contemporary issues of wind engineering is presented.